2022
DOI: 10.3389/fped.2022.813638
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Risk Factors of Severe Pneumonia in Children With Acute Lymphoblastic Leukemia

Abstract: ObjectiveThis study aims to analyze the clinical characteristics of pediatric acute lymphoblastic leukemia (ALL) complicated by pneumonia and the risk factors of severe cases to preliminarily construct a prediction model for ALL complicated by severe pneumonia.MethodsA retrospective analysis was carried out on the clinical data of children diagnosed with ALL complicated by pneumonia hospitalized at the Department of Pediatrics of the Affiliated Hospital of Southwest Medical University between January 2013 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…38 Successful outcomes have been reported for other invasive mycoses or severe infection when patients with profound neutropenia were supported with granulocyte transfusions. [39][40][41][42][43] Anemia can damage a child's immune system and exacerbate the risk of infections. There is evidence suggesting that red blood cells are directly involved in the maintenance of innate and adaptive immune systems and are modulators of T-cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 Successful outcomes have been reported for other invasive mycoses or severe infection when patients with profound neutropenia were supported with granulocyte transfusions. [39][40][41][42][43] Anemia can damage a child's immune system and exacerbate the risk of infections. There is evidence suggesting that red blood cells are directly involved in the maintenance of innate and adaptive immune systems and are modulators of T-cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro results showed that granulocytes retained function and rapidly migrated to the site of infection despite a short half‐life 38 . Successful outcomes have been reported for other invasive mycoses or severe infection when patients with profound neutropenia were supported with granulocyte transfusions 39–43 . Anemia can damage a child's immune system and exacerbate the risk of infections.…”
Section: Discussionmentioning
confidence: 99%
“…Lung involvement in children with acute leukemia is typical during the acute phase of chemotherapy [5,6]. Among the main causes of these complications, there are immunosuppression and cytopenia [8,9], caused both by the underlying disease and myelosuppressive effects of chemotherapy, direct cytotoxic effect of drugs on lung tissue [10], blast infil-tration of the lungs on the background of hyperleukocytosis [11]. Among documented infection episodes, the respiratory system was the most common site [12,13].…”
Section: Introductionmentioning
confidence: 99%